2018
DOI: 10.1007/s10825-018-1192-y
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of electronic performance, half-metallicity, and magnetic properties of Cr-substituted BaTe

Abstract: We have investigated the structural, electronic, and ferromagnetic properties of chromium (Cr)-doped rocksalt BaTe (Ba 1−x Cr x Te) compounds with compositions x = 0.25, 0.5, and 0.75, based on density functional theory with generalized gradient approximation of Wu-Cohen (GGA-WC) and Tran-Blaha-modified Becke-Johnson (TB-mBJ) potential using the WIEN2k package. We found that the electronic structure showed half-metallic ferromagnetic character with spin polarization of 100 % around the Fermi level. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The result of wide-indirect gap of 5.392 eV of CaO is in good agreement with recent calculated value of 5.35 eV of Tran and Blaha ( 2017 ) study using the same TB-mBJ potential (Becke and Johnson, 2006 ; Tran and Blaha, 2009 ), and it is better than the values ranging from 3.437 to 3.67 eV of Fan et al ( 2015 ), Nejatipour and Dadsetani ( 2015 ), Yang et al ( 2016 ), Tran and Blaha ( 2017 ), Salam ( 2018 ) found by the LDA (Perdew and Zunger, 1981 ; Perdew and Wang, 1992 ), GGA-WC (Wu and Cohen, 2006 ), GGA-PBE (Perdew et al, 1996 ), and GGA-PBEsol exchange potentials (Perdew et al, 2008 ). The TB-mBJ provides accurate gap for CaO because he is known for its performance in the calculation of electronic structures of insulators and semiconductors with respect to LDA and all forms of GGA approximations (Bhattacharjee and Chattopadhyaya, 2017a , b ; Chattopadhyaya and Bhattacharjee, 2017 ; Berriah et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The result of wide-indirect gap of 5.392 eV of CaO is in good agreement with recent calculated value of 5.35 eV of Tran and Blaha ( 2017 ) study using the same TB-mBJ potential (Becke and Johnson, 2006 ; Tran and Blaha, 2009 ), and it is better than the values ranging from 3.437 to 3.67 eV of Fan et al ( 2015 ), Nejatipour and Dadsetani ( 2015 ), Yang et al ( 2016 ), Tran and Blaha ( 2017 ), Salam ( 2018 ) found by the LDA (Perdew and Zunger, 1981 ; Perdew and Wang, 1992 ), GGA-WC (Wu and Cohen, 2006 ), GGA-PBE (Perdew et al, 1996 ), and GGA-PBEsol exchange potentials (Perdew et al, 2008 ). The TB-mBJ provides accurate gap for CaO because he is known for its performance in the calculation of electronic structures of insulators and semiconductors with respect to LDA and all forms of GGA approximations (Bhattacharjee and Chattopadhyaya, 2017a , b ; Chattopadhyaya and Bhattacharjee, 2017 ; Berriah et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The alkaline earth (II-VI) chalcogenides are the most significant materials having wide range usage in solar cells, photoconductors, laser diodes, IR detectors, light emitting diode and magneto optical devices etc [4]. The Ba chalcogenides (II-VI family) such as BaX (S, Se, and Te) are convenient host semiconductor for spin-based materials [5,6]. Under normal cases, these alloys exist with closed shell ionic coordination in NaCl-type (B1) configuration.…”
Section: Introductionmentioning
confidence: 99%
“…A total magnetic moment of 3 µ B is obtained, being produced mainly by the V atoms. Similarly, large variety of DMS materials have been considered, including Ba 1−x Cr x Te [16], Ba 1−x V x S [17], Al 0.75 Mn 0.25 Y (Y = N, P, As) [18], and Ca 1−x Cr x S [19], among others. Revising the literature, we realized that in most cases only semiconductors are employed as host for doping, while insulators with large band gap have not been considered yet.…”
Section: Introductionmentioning
confidence: 99%